2001
DOI: 10.1159/000047605
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Function in Patients with Acute Brainstem Stroke

Abstract: Dysfunction of the autonomic nervous system (ANS) often complicates the clinical course in patients with acute stroke. The studies of the function of ANS in patients with brainstem stroke are scarce. The purpose of our study was to evaluate the function of ANS in the early period after acute brainstem stroke and to find out whether the location of stroke in brainstem influences the function of ANS. We studied heart rate variability (HRV) and plasma levels of catecholamines in 14 eligible patients with medullar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 20 publications
(26 reference statements)
1
29
0
2
Order By: Relevance
“…43 Heart-rate variability has been used to quantify autonomic dysfunction across a broad spectrum of TBI severity, including concussion. 33,44,45 Autonomic dysfunction after TBI is believed to represent some degree of uncoupling between the brain autonomic centers and the cardiovascular system, 44 can be precipitated by different types of exercise in patients after concussion, 28,33 and improves as patients recover from severe TBI 46 or from concussion. 28 One group, for example, showed that concussed athletes who reported recent symptom resolution had abnormal HRV 33 and elevated heart rates (HRs) 34 during steady-state exercise (but not at rest) versus healthy controls, which is consistent with increased SNS activation during exercise after concussion.…”
Section: The Physiology Of Concussionmentioning
confidence: 99%
“…43 Heart-rate variability has been used to quantify autonomic dysfunction across a broad spectrum of TBI severity, including concussion. 33,44,45 Autonomic dysfunction after TBI is believed to represent some degree of uncoupling between the brain autonomic centers and the cardiovascular system, 44 can be precipitated by different types of exercise in patients after concussion, 28,33 and improves as patients recover from severe TBI 46 or from concussion. 28 One group, for example, showed that concussed athletes who reported recent symptom resolution had abnormal HRV 33 and elevated heart rates (HRs) 34 during steady-state exercise (but not at rest) versus healthy controls, which is consistent with increased SNS activation during exercise after concussion.…”
Section: The Physiology Of Concussionmentioning
confidence: 99%
“…Essa condição pode estar relacionada ao fato dessas adaptações caracterizarem uma situação transitória 28 e/ou estarem relacionadas à independência funcional, ou seja, é possível que indivíduos mais independentes recuperem a VFC mais rapidamente 29 . E, mesmo na presença de fatores de risco tradicionais para o AVE, como dislipidemias, hipertensão arterial e hiperglicemia, que prejudicam a modulação autonômica da frequência cardíaca 30 , como mostra o estudo de Hägglund et al 31 ao observar menor atividade parassimpática em indivíduos com diabetes tipo 1, neste estudo não foram observadas alterações pertinentes.…”
Section: Dados Antropométricos E Fisiológicosunclassified
“…Tais divergências podem estar relacionadas ao fato dessas adaptações caracterizarem uma situação transitória 27 e/ou estarem relacionadas à independência funcional, ou seja, é possível que indivíduos mais independentes recuperam a VFC mais rapidamente 28 . Além disso, tem sido verificado que a presença de fatores de risco tradicionais para o AVE pode prejudicar a modulação autonômica cardíaca 26 , entretanto, não foi encontrada associação entre os índices de baixa (BF) e alta frequência (AF) com dislipidemia, hiperglicemia, obesidade e hipertensão presentes nos sujeitos estudados.…”
Section: Média ± Desvio Padrão Valores De Referênciaunclassified